KEMAMPUAN PETANI DALAM USAHATANI PADI SAWAH DI DESA RONTA KECAMATAN BONEGUNU KABUPATEN BUTON UTARA - Monalisa, Monalisa; Hamzah, Awaluddin; Suriana, Suriana (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
Rice is a major food commodity that plays a vital role in Indonesia's food security, but its productivity in Ronta Village is still low due to farmers' limited ability to manage rice farming. The purpose of this study was to determine the ability of farmers in rice farming activities in Ronta Village, Bonogunu District, North Buton Regency. The research population consisted of all paddy farmers in Ronta Village, totaling 14 farmers. The sample was determined using the census method. Research data were collected using interviews, documentation, and surveys using questionnaires. The variables observed in this study were farmers' capabilities, specifically their knowledge and skills in paddy farming. The collected data was then processed using quantitative descriptive analysis. The results showed that rice farmers in Ronta Village had high knowledge and skills in rice cultivation, including land preparation, seedling cultivation, planting, fertilization, irrigation, and harvesting. The farmers' knowledge was in the good category (100%), as demonstrated by their understanding of cultivation techniques and the use of high-quality seeds, while the skills of the majority of farmers (85.71%) were classified as skilled with the appropriate application of modern and traditional methods. The farmers' capabilities are an important asset for increasing the productivity and efficiency of farming.